The prevalance of binge eating disorder and associated psychiatric and substance use disorders in a student population in Kenya – towards a public health approach - Mutiso, Victoria N.; Ndetei, David M.; Muia, Esther N; Alietsi, Rita K; Onsinyo, Lydia; Kameti, Frida; Masake, Monicah; Musyimi, Christine; Mamah, Daniel (My University, 2022)
Introduction: Kenya in particular and Africa in general lack data on Binge Eating Disorder (BED). The overarching objective of this study is to fll that gap. Kenyans may not be aware that BED exists when a “very good” appetite is considered a sign of good health, especially if food is available either at home, in fast food shops or when communally eating together, a very common cultural practice. On the other hand where there is relatively insufcient food, it is not expected that one could be having a problem of eating too much. Method: We administered the following tools and measurements to 9742 participants (high school, college and university students): 1) Researcher designed socio-demographic and economic indicator questionnaire; 2) An instrument documenting DSM-IV diagnostic criteria for BED and its various symptoms; 3) An instrument to determine DSM-IV psychiatric disorders and substance abuse;4) An instrument measuring high risk for psychosis ,afectivity and stress; 5) A WHO designed instrument measuring the severity of substance abuse for specifc substances. We used descriptive and inferential analysis to determine the prevalence and association of the diferent variables. Independent predictors of BED were generated from a generalized linear model (p<0.05). Results: We found a prevalence of 3.2% of BED and a wide range of prevalence for BED and BED related symptoms (8.1% to 19%). The least prevalent was "To prevent weight gain from eating binge did you force yourself to vomit, or used laxatives?”. The most common was "Did you often go on eating binges (eating a very large amount of food very quickly over a short period of time)." Major depression, obsessive compulsive disorder, panic disorder, agoraphobia, generalized anxiety disorder ,a positive stress screen and drug abuse were independent predictors of BED (p<0.05). Conclusion: Our fndings on the prevalence of BED and signifcant associations with various psychiatric disorders and substance use disorders are similar to those obtained in High Income Countries (HIC) using similar large-scale samples in non-clinical populations. Our fndings suggest the need fora public health approach to enhance awareness of BED and to promote health-seeking behaviour towards management of BED.
Keywords: Eating Disorders; Binge Eating; Co-morbidity; Kenya